Pengaruh Model Pembelajaran Direct Instruction Dalam Pendidikan Jasmani Terhadap Tingkat Adversity Quotient (AQ) Siswa - Rola Angga Lardika; Singha Tulyakul (Journal Sport Area, 2020)
The purpose of this study is to determine the significance towards the effects of direct instruction in physical education and problem-solving skills to solve the problems faced by students (Adversity Quotient). The method applied is through group experiment using pretest and posttest design. The procedure for this research include observation, interview, treatment program preparation, analysis and conclusion. The research findings are achieved through group experiment with direct instruction model with significant influence towards students’ adversity quotient level with a score of (sig.), 000 < α=0,005. Based on the data, it can be concluded that the direct instructional model provide significant effect towards the level of students’ adversity quotient.